2016
DOI: 10.1038/srep32035
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of serum IgG4 level for IgG4-related disease: a meta-analysis

Abstract: An elevated serum IgG4 level is one of the most useful factors in the diagnosis of IgG4-related disease (IgG4-RD). In this study, we performed a meta-analysis of the published articles assessing the diagnostic accuracy of serum IgG4 concentrations for IgG4-RD. The databases of MEDLINE/PubMed, EMBASE and Web of Science were systematically searched for relevant studies. Sensitivities and specificities of serum IgG4 in each study were calculated, and the hierarchical summary receiver operating characteristic (HSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
0
21
0
2
Order By: Relevance
“…Serum IgG4 level exhibits sensitivity ranging from 82.3% to 89.3% and a specificity of 94.6% to 95.8% [16]. Its positive predictive value in diagnosing ranges from 36% to 79% [16]. Moreover, this predictive value does not correspond with the cut-off value of the IgG4 level [17].…”
Section: Serological Findingsmentioning
confidence: 96%
See 2 more Smart Citations
“…Serum IgG4 level exhibits sensitivity ranging from 82.3% to 89.3% and a specificity of 94.6% to 95.8% [16]. Its positive predictive value in diagnosing ranges from 36% to 79% [16]. Moreover, this predictive value does not correspond with the cut-off value of the IgG4 level [17].…”
Section: Serological Findingsmentioning
confidence: 96%
“…Eosinophilia and increased serum IgE level are reported more frequently in IgG4-related lacrimal gland enlargement and overlapping asthma-like symptoms. These findings can be explained by the enhanced Th2 cell differentiation and IL-10 production in the pathogenesis of IgG4-related lacrimal gland enlargement [16]. Thrombocytopenia rarely occurs in MD in contrast to SS [18].…”
Section: Serological Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…44 A meta-analysis of 23 studies comprising 6048 patients found that serum level of IgG4-RD detected IgG4-RD with a pooled sensitivity of 85% (95% CI, 78%-90%) and a pooled specificity value of 93% (95% CI, 90%-95%). 45 Limitations of such analyses, which are acknowledged in the study, include patient inclusion bias and variable methods of measurement of serum IgG4, as well their varying upper limits of normal. Use of fold-normal rather than absolute value for serum IgG4 is more appropriate until there is an agreed-upon standard for its measurement.…”
Section: Serum Levels Of Igg4mentioning
confidence: 99%
“…Great mimickers of IgG4-RD including pancreatic adenocarcinoma, lymphoma, and ANCA associated vasculitis can present with elevated serum IgG4 levels while biopsy confirmed IgG4-RD patients can have normal IgG4 concentrations. A meta-analysis of predominantly Caucasian and Asian patients did not reveal a specific cut off value for serum IgG4 level to diagnose IgG4-RD, but did find significantly high pooled sensitivity and specificity for serum IgG4 level testing (25). However, another study has shown specificity and positive predictive value of elevated serum IgG4 concentrations to be 60% and 34% respectively (26).…”
Section: - Diagnosismentioning
confidence: 99%